Effect of CO2 addition on gas composition of synthesis gas from catalytic gasification of low rank coals. (15th July 2015) - Sharma, Atul; Matsumura, Akimitsu; Takanohashi, Toshimasa
Highlights: Reduced operation temperature for gasification. Separate stages for catalytic gasification and catalytic tar cracking. Control of H2 /CO ratio of the synthesis gas in a continuous operation. K2 CO3 was very effective as tar cracking/gasification catalyst. Predicted synthesis gas composition matched the experimental values. Abstract: This paper reports the development of a catalytic gasification process to gasify low rank coals to produce FT-suitable synthesis gas in a single direct step using K2 CO3 as a catalyst and a mixture of steam and CO2 as a gasifying agent. A small laboratory scale continuous catalytic gasification unit was developed and experiments were carried out at 700 °C. Effect of CO2 addition on the synthesis gas composition was investigated. Synthesis gas with H2 /CO = 1, 2 and 3 was produced by changing the steam/CO2 ratio of the gasifying agent. Calculated gas compositions were found to be in good agreement with the experimental gas compositions suggesting that the water–gas shift reaction was in thermodynamic equilibrium. K2 CO3 was also very effective for tar cracking. The results showed that the synthesis gas suitable for the FT synthesis process can be produced in a single step at 700 °C by steam/CO2 gasification process.